Effect of wheat bran supplementation on feed intake, body weight change and retained energy in the carcass of Ethiopian highland Zebu (Bos indicus) oxen fed teff straw (Eragrostis tef) as basal diet - Wolde-Michael, T.; Osuji, P.O.; Yimegnuhal, A.; Yami, A. (Ethiopian Society of Animal Production, 2002)
The experiment was carried-out at the ILRI Debre Zeit Research Station in Ethiopia. Sixty three Ethiopian Highland Zebu Bos indicus) oxen were ranked by weight and blocked in a completely randomized block design. Nine representative oxen from various blocks were slaughtered as the initial slaughter group while the remaining 54 oxen were allocated to three levels of supplementation, low, medium and high. The animals were individually fed a diet consisting of tef j' straw ad libitum as roughage and wheat bran as supplement fed at 0.75, 2.75 and 4.75 kg head -1 day -1 for 145 days. Live-weight was recorded every two weeks. At the end of the experimental period 6 oxen from each feeding level were slaughtered and dissected into the component parts. Supplementation had a significant effect (p<0.001) on tef j' straw and total dry matter (DMI) and organic matter intakes (OMI). Both DMI and OMI increased with increasing supplementation, however, tef f'straw intake increased from low to medium and then decreased. Supplementation increased body weight gain (p<0.001). The average body weight gain BWG) were 68, 459 and 477 (+ or -) 27.6 g/day for the low, medium and high levels of supplementation respectively. The medium group performed well in terms of feed conversion efficiency and cost of dry matter per kg body weight. The data indicated that supplementation had significant effect on empty body weight change (EBWC) (p<0.001), muscle fat (p<0.01) and energy retained in the carcass. The medium group gained the most muscle fat (MFG) and retained more energy (ER) in the carcass.